Community Integration After Traumatic Brain Injury and Related Factors: A Study in the Nepalese Context - Sumana Lama BSN, RN; Jintana Damkliang PhD, RN; Luppana Kitrungrote PhD, RN (SAGE Publishing, 2020)
Introduction Community integration is an essential component for rehabilitation among traumatic brain injury (TBI) survivors, which yields positive outcomes in terms of social activities, community participation, and productive work. A factor that usually facilitates community integration among TBI survivors is social support, whereas physical environment and fatigue are most often found as barriers. Objectives This study aimed to (1) describe the level of community integration, fatigue, physical environment, and social support of persons after TBI, and (2) examine the relationship between community integration and these three factors. Methods This is a descriptive correlational study. One hundred and twenty TBI survivors living in the communities of Province Number Three, Nepal were enrolled using the stratified sampling technique. The data were collected using the Community Integration Questionnaire, Modified Fatigue Impact Scale, Craig Hospital Inventory of Environmental Factors, and the Multidimensional Scale of Perceived Social Support. Descriptive statistics and Pearson's correlation were used to analyze the data. Results Community integration, fatigue, and physical environment showed a moderate level, while social support revealed a high level. Fatigue was significantly correlated with overall community integration, whereas physical environment was found to correlate with two subscales of community integration, home integration and productive activities. Conclusion To enhance the level of community integration among TBI survivors, health care providers, in particular rehabilitation nurses and community nurses, should plan and implement strategies such as follow-up appointments or continued rehabilitation at home.